Advances in Artificial Life, Evolutionary Computation and Systems Chemistry 10th Italian Workshop, WIVACE 2015, Bari, Italy, September 22-25, 2015, Revised Selected Papers - Rossi, Federico; Mavelli, Fabio; Stano, Pasquale; Caivano, Danilo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book constitutes the revised selected papers of the 10th Italian Workshop on Advances in Artificial Life, Evolutionary Computation and Systems Chemistry, WIVACE 2015, held at Bari, Italy, in September 2015. The 18 papers presented have been thoroughly reviewed and selected from 45 submissions. They cover the following topics: evolutionary computation, bioinspired algorithms, genetic algorithms, bioinformatics and computational biology, modeling and simulation of artificial and biological systems, complex systems, synthetic and systems biology, systems chemistry.
Evolutionary computation -- Bioinspired algorithms -- Genetic algorithms, bioinformatics and computational biology -- Modeling and simulation of artificial and biological systems -- Complex systems, synthetic and systems biology -- Systems chemistry.
Keywords: Computer science; Computers; Computer science -- Mathematics; Artificial intelligence; System theory; Computer Science; Mathematics of Computing; Artificial Intelligence (incl. Robotics).; Complex Systems; Theory of Computation; Electronic books